Manāẓir ʿĀšiq Hargānvī ke adabī darīce - Betāb, ʿIšrat (Ejūkešnal Pablišing Hāʾūs, 2020)
On the works of Manāẓir ʻĀshiq Hargānvī, born 1947, Urdu scholar and critic.
Der Paralleltitel ist eine Umschrift von der Rückseite der Haupttitelseite und vom hinteren Buchumschlag
Keywords: ʻĀshiq Hargānvī; Manāz̤ir; 1947-; Urdu literature; 20th century; History and criticism.